2023
DOI: 10.1186/s12967-023-04454-3
|View full text |Cite
|
Sign up to set email alerts
|

DARS2 overexpression is associated with PET/CT metabolic parameters and affects glycolytic activity in lung adenocarcinoma

Xu-Sheng Liu,
Ling-Ling Yuan,
Yan Gao
et al.

Abstract: Background This study investigated the correlation between the expression of DARS2 and metabolic parameters of 18F-FDG PET/CT, and explored the potential mechanisms of DARS2 affecting the proliferation and glycolysis of lung adenocarcinoma (LUAD) cells. Methods This study used genomics and proteomics to analyze the difference in DARS2 expression between LUAD samples and control samples. An analysis of 62 patients with LUAD who underwent 18F-FDG PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that enhanced glycolytic activity in tumor cells correlates positively with 18 F-FDG uptake. Thus, by measuring the uptake values of 18 F-FDG (SUV), one could indirectly reflect the glycolytic activity and metabolic status of the tumor cells 44 47 . In our current study, analysis of the GSE110224 dataset revealed a positive correlation between TRIP6 expression and 18 F-FDG metabolic parameters (SUV), suggesting that an increase in TRIP6 expression could potentially lead to significant changes in SUV levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that enhanced glycolytic activity in tumor cells correlates positively with 18 F-FDG uptake. Thus, by measuring the uptake values of 18 F-FDG (SUV), one could indirectly reflect the glycolytic activity and metabolic status of the tumor cells 44 47 . In our current study, analysis of the GSE110224 dataset revealed a positive correlation between TRIP6 expression and 18 F-FDG metabolic parameters (SUV), suggesting that an increase in TRIP6 expression could potentially lead to significant changes in SUV levels.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, observation and image analysis were conducted using a fluorescence microscope. For a detailed experimental protocol, please refer to our previous research 40 …”
Section: Methodsmentioning
confidence: 99%
“…Once their density reached 70-80%, the siRNA was transfected into cells using Lipofectamine 3000 transfection reagent (L3000015, Invitrogen). For a detailed experimental protocol, please refer to our previous studies [30].…”
Section: Cell Culture and Sirna Transfectionmentioning
confidence: 99%